The study of influencing factors on working capability of “Agco sisu power” engine utilized for crop production in Mongolia (Mongolian Journal of Agricultural Sciences, 2018)
Due to our country’s weather conditions and improper exploitation of these macheries, there has been occurring series of technical failure, and the down state of the power machinery equipped with smart system CRD engine. Moreover, technical idle and the product cost industrial has been increased.As a result of above mentioned problem, we need to use efficiently the technical resource of agricultural power machines with CRD engine.The aim of our research work was to determine the factors influencing on engine working power, to increase the technical resource and to use it efficiently.Within the frame work of our research study, we are introducing the determination of the influencing factors of working capability of engine in field case, and the result of the laboratory testing the and plan model.“Agco sisu power” Хөдөлгүүрийн ажлын чадварт нөлөөлөх хүчин зүйлийн судалгааХураангуй: Монгол орны нөхцөлд ХАА-н зүтгэх хүчний машины CRD хөдөлгүүрийн техникийн нөөцийг бүрэн ашиглах, шинэ техник технологийг нутагшуулан тогтвортой үйлдвэрлэлийг хангах явдал зүй ёсоор тулгарч байна. Иймд уг хөдөлгүүрийн ажлын чадварт нөлөөлөх хүчин зүйлсийг тогтоох, нөөцийг нэмэгдүүлэх, бүрэн ашиглах зорилгоор уг судалгааг гүйцэтгэсэн болно. Энэхүү судалгааны ажлын хүрээнд бид талбайн нөхцөлд хөдөлгүүрийн ажлын чадварт нөлөөлөх хүчин зүйлсийг тогтоож лабораторийн туршилт төлөвлөлтийн загварыг гаргасан үр дүнг танилцуулж байна.Түлхүүр үг: CRD хөдөлгүүр, ажлын чадвар, саатал, хүчин зүйл, туршилт